The Values Of Silaturahim Character Education In The Local Wisdom Tradition Of Hari Rayo Enam In The Community Of Ujung Pasir Village, Tanah Cogok Sub-District - Netral, Lidia; Masnur Alam, Masnur Alam; Muhamad Yusuf, Muhamad Yusuf; Wisnarni, Wisnarni (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This study aims to examine the character education values embedded in the practice of silaturahim (strengthening kinship) within the local wisdom tradition of Hari Rayo Enam in Ujung Pasir Village, Tanah Cogok Sub-district. This tradition is a hereditary celebration with deep social and religious significance. The community uses this moment to strengthen family ties, build communication, and instill values of togetherness and solidarity. Using an ethnopedagogical approach, this research found that the Hari Rayo Enam tradition reflects character education values such as togetherness, cooperation, care, family spirit, and solidarity. Activities such as congregational Tasbih prayers, grave visits, recitation of Yasin and tahlil, and other social activities strengthen the integration of these character values into community life. The roles of community leaders, religious figures, the village head, and traditional leaders are crucial in preserving this tradition. This study concludes that the Hari Rayo Enam tradition is not only a religious celebration but also an important means of building character and strengthening social relationships, which can be used as a model for implementing character education in various aspects of life.